Immigration - Haugen, David M., 1969-; Musser, Susan; Lovelace, Kacy. (Detroit : Greenhaven Press, 2009)
A compendium of viewpoints--both pro and con--on several issues relating to immigration in American society.
How does immigration affect the United States? Immigration benefits the economy / Becky Akers and Donald J. Boudreaux ; Illegal immigration hurts the economy / Art Thompson ; Immigration harms African American workers / Frank Morris -- Immigration alone does not harm U.S. workers / Rakesh Kochhar ; Immigrants burden Social Services / Steven A. Camarota ; Immigrants do not burden Social Services / Shikha Dalmia -- How should the United States contend with its nonnative speakers? English should be America's official language / Kenneth Blackwell -- Efforts to make English America's official language hide bigotry / Lloyd Garver ; English immersion education benefits immigrant children / Christine Rossell ; English immersion education is flawed / Margaret Adams and Kellie M. Jones -- How should the United States deter illegal immigration? A border fence will deter illegal immigration / Duncan Hunter ; A border fence will not deter illegal immigration / Melanie Mason ; Employment verification will deter illegal immigration / Robert E. Rector ; Employment verification will not deter illegal immigration / Tom DeWeese ; The United States should adopt open immigration / Harry Binswanger ; The United States should not adopt open immigration / Vin Suprynowicz ; Lax immigration policies invite terrorism / Mark Krikorian -- Does immigration threaten national security? The visa waiver program is a security threat / Dan Stein ; The visa waiver program is not a security threat / Daniel Griswold ; Aliens who overstay their visas are a serious security threat / Jessica M. Vaughan ; Aliens who overstay their visas are not a serious security threat / Margaret D. Stock ; Illegal immigrants are a threat to national security / Jan C. Ting.
Includes bibliographical references and index.
Keywords: United States -- Emigration and immigration; Immigrants -- United States; Illegal aliens -- United States; United States -- Emigration and immigration; Immigrants; Illegal aliens; Emigration and immigration; Illegal aliens; Immigrants; United States; United States -- Immigration and emigration